Analisis Kebutuhan Pengembangan Modul Pembelajaran Fisika Materi Lapisan Bumi Terintegrasi Mitigasi Bencana Berbasis Kearifan Lokal - Nurpatri, Yeni; Maielfi, Dini; Indrawati, Ena Suma; Widya, Widya; Yusmanila, Yusmanila (Kappa Journal, 2023)
This research is motivated by the condition of West Sumatra province is an area prone to natural disasters, so early prevention is needed by providing students with insight into disaster mitigation through physics learning. This research uses a descriptive research method and a questionnaire as a data collection technique. The subjects in this research were students and 5 teachers from 3 junior high schools in Padang City. Data was collected to obtain the results of a media needs analysis through observation and questionnaires. The research results show that the development of modules on earth layers material integrated with natural disasters integrated with local wisdom is very necessary to support the physics learning process. This can be seen from several aspects of the research described in the questionnaire. The results of the questionnaire show that it is very important for students to have insight into mitigation